Pemberdayaan Nelayan melalui Optimalisasi Karamba Tancap Multifungsi untuk Mendukung Wisata Bahari di Desa Pamata Raya, Kendari - Ermayanti Ishak; Ratna Diyah Palupi; . Disnawati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The village of Pamata Raya is a coastal area near from tourism of Bokori Island. This community service in collaboration with students field work practice program of faculty of fisheries and marine science Halu Oleo University aimed to provide knowledge and to empowerment community through the optimize a pen culture activity into a multifunctional facilities, such as for rear of fish, marine tourism, and education. The activity was conducted for July 2017 and consists of two steps, which is technical guidance to making a pilot multifunctional pen culture and training to make various food value added products based on fish. The results of the community service programs have been built multifunctional pen culture (9 m2) which is equipped with gazebos as a tourist spot for fishing, culinary, and education. This pen culture is used to cultivated various species of reef fish (mullet fish, parrotfish, groupers, and lobsters). Furthermore, culinary tourism is carried out by training fish-based food processing by groups of women fishermen, such as of fish meat floss, fish meatballs, and fish nuggets. Successfully this program can be obtained from the increased participation of partner in program implementation, the improvement of the quality of human resources through the transfer of technology, and economically there has been an increase in fish production and fishermen’s income especially for the target groups. This multifunctional pen culture can be an alternative fishermen livelihood during high wave season. The presence of multifunctional pen culture indirectly increase the number of visitors in Bokori Island which was also beneficial to the local community.